Spatial Ecology and Seasonal Habitat Use of the King Rail (Rallus elegans) along the Atlantic Coast - Kolts, Jaan Runyon (East Carolina University, 2014)
TThe King Rail (Rallus elegans) continues to experience population declines throughout its range. Due to its secretive nature and occupancy of densely vegetated marshes, little is known about the behavior and ecology of the King Rail. Moreover, conservation efforts lack essential information about King Rail habitat use to make informed decisions, especially along the Atlantic coast and during the non-breeding period. To address this, radio-telemetry was used to elucidate the spatiotemporal patterns of movement and habitat preferences of King Rails throughout the year. The microhabitat characteristics were quantified at nest locations and where adults were located during the breeding and non-breeding periods, including the poorly understood brood-rearing period. Nest densities were greatest in areas with high interspersion of emergent vegetation and open water, and most rails selected nest sites in Juncus roemerianus patches, the predominant species of emergent vegetation. Adults traveled with their broods substantial distances from nest locations, as much as 1 kilometer within the first week post-hatching, to areas with less Juncus roemerianus and with shallower water than where they nested. During the non-breeding and brood-rearing periods, adults were found closer to edges of open water and emergent vegetation than during the nesting period, areas thought to provide increased foraging opportunities. Empirically, it was determined for the first time that adults use wooded and shrubby marsh during the brood-rearing and non-breeding periods. This habitat type has not been considered under current King Rail management plans. Observations spanning the entire year documented the movements of King Rails and revealed that at least part of the population is resident. Mean home range size was 19.8±2.5 ha (95% kernel density). Individual home range sizes did not differ significantly between seasons. There was evidence of sexual segregation in habitat use during the non-breeding period. Females had significantly larger home ranges than males and tended to travel greater distances. During the non-breeding season, all birds captured in emergent marsh were male, and radio-tagged females were found using adjacent wooded marsh. Adults used both managed impoundments and emergent natural marsh at all times of the year, but increased their use of impoundments immediately following drawdown, and while brood-rearing, especially when water levels rose abruptly in natural marsh. In coastal habitats prone to variation in water level, provision of impoundments with sluice control adjacent to natural marsh appears to be of benefit to brood-rearing King Rails. Where populations are present year-round, habitat management should emphasize interspersion of patches of emergent vegetation with pockets of open water providing a mosaic of cover and appropriate nest sites in proximity to foraging areas. Scrub-shrub and wooded wetland habitat at the perimeter of emergent marsh may favor residency of overwintering King Rails of both sexes. These findings highlight the need for conservation efforts to consider the habitat preferences and spatial distribution of King Rails throughout the year and at all life stages.
Keywords: Biology; King rail--Atlantic Coast (America); Bird declines--Atlantic Coast (America)